Faktor Determinan Pengangguran di Indonesia: Apakah Program Kartu Prakerja Menjadi Katalisator Penurunan Pengangguran? - Adam, Asep Muhammad; Nugraha, Galih; Hanapia, Asep Yusup; Noven, Sarah Annisa; Rusliana, Nanang (SAFE-Network, 2025)
Unemployment remains a major issue in Indonesia's development, especially among vocational education graduates. This study examines the effect of the Pre-Employment Card Program in reducing the unemployment rate. This study uses data from the 2023 National Labor Force Survey (Sakernas) with logistic regression model analysis. The number of samples used was 1,481, consisting of 201 unemployed groups and 1,280 employed groups. Results show that apprenticeship experience and vocational education background significantly reduce the risk of unemployment, while the Pre-Employment card program and certified training show no significant impact. Higher education and income are negatively correlated with unemployment, while women are more at risk of unemployment. The findings emphasize the importance of practical experience and vocational education strategies that match labor market needs. This study provides insights for labor policies in developing countries.